2004
DOI: 10.1088/0031-9155/49/17/009
|View full text |Cite
|
Sign up to set email alerts
|

Spectral components of laser Doppler flowmetry signals recorded in healthy and type 1 diabetic subjects at rest and during a local and progressive cutaneous pressure application: scalogram analyses

Abstract: A significant transient increase in laser Doppler flowmetry (LDF) signals is observed in response to a local and progressive cutaneous pressure application in healthy subjects. This reflex may be impaired in diabetic patients. The work presents a signal processing providing the clarification of this phenomenon. Scalogram analyses of LDF signals recorded at rest and during a local and progressive cutaneous pressure application are performed on healthy and type 1 diabetic subjects. Three frequency bands, corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…Our previous scalogram study of healthy and type 1 diabetic subjects showed that neurogenic and endothelial-related metabolic activities are significantly higher during progressive pressure than at rest. 17 However, the relative contribution of the endothelialrelated metabolic activity is significantly higher during the progressive pressure increase than at rest, in the interval 200-400 s following the beginning of the pressure application, but only for healthy subjects. 17 In combination, these two studies can be taken to imply that one pair of exponents of high absolute value reflects endothelial-related metabolic activities.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our previous scalogram study of healthy and type 1 diabetic subjects showed that neurogenic and endothelial-related metabolic activities are significantly higher during progressive pressure than at rest. 17 However, the relative contribution of the endothelialrelated metabolic activity is significantly higher during the progressive pressure increase than at rest, in the interval 200-400 s following the beginning of the pressure application, but only for healthy subjects. 17 In combination, these two studies can be taken to imply that one pair of exponents of high absolute value reflects endothelial-related metabolic activities.…”
Section: Resultsmentioning
confidence: 95%
“…17 However, the relative contribution of the endothelialrelated metabolic activity is significantly higher during the progressive pressure increase than at rest, in the interval 200-400 s following the beginning of the pressure application, but only for healthy subjects. 17 In combination, these two studies can be taken to imply that one pair of exponents of high absolute value reflects endothelial-related metabolic activities. The results of this study could explain the high prevalence for diabetic patients to develop plantar ulcers.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Time and spatial invariance means that, for each characteristic frequency band of the signal, no statistical difference is found for the energy between the two different time intervals, nor between the site analyzed. 2,3,[9][10][11] To study time and spatial variations, it is therefore necessary to analyze the spectrum of impedance signals. However, impedance signals are weakly stationary, i.e., the characteristic frequencies of the signals slightly change continuously.…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…Many organs can be investigated with the LDF technique: kidney, liver, intestines, brain, skin. Moreover, the clinical applications are numerous: diabetes microangiopathy, flap monitoring, peripheral vascular disease, plastic surgery, Raynaud's phenomenon, thermal injury (see for example Ray et al, 1999;Humeau et al, 2004;Ziegler et al, 2004;Yamamoto-Suganuma & Aso, 2009;Merz et al, 2010;Smit et al, 2010). Due to the poor predictability of tissue perfusion for given location and time, LDF signals are rarely recorded in basal conditions.…”
Section: Introductionmentioning
confidence: 99%